# SOLUTION: Hi, I do not understand how to reduce or when to reduce the fraction within the quadratic equation. I came up with this answer. Would you please show me how to reduce for the fin

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: Hi, I do not understand how to reduce or when to reduce the fraction within the quadratic equation. I came up with this answer. Would you please show me how to reduce for the fin      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Question 411026: Hi, I do not understand how to reduce or when to reduce the fraction within the quadratic equation. I came up with this answer. Would you please show me how to reduce for the final answer? Thanks. -x^2+6x-21=0 (-1)-x^2+6x-21=0(-1) x^2+6x-21=0 -6+-sqrt((6)^2-4(1)(-21))/2(1) -6+-sqrt(36+84)/(2) -6+-sqrt(120)/(2) -6+-sqrt(6(20))/(2) -6+-sqrt(6)/(2) -6+- 20 sqrt(6)/(2) -?+- sqrt(6)/(10) (thought we divide -6/20 then divide 2/20) leaves the 6 Found 2 solutions by edjones, ewatrrr:Answer by edjones(7569)   (Show Source): You can put this solution on YOUR website!a=-1, b=6, c=-21 x=(-6+-sqrt(36-4*21))/-2 not /2 and not -4(1)(-21) should be -4(-1)(-21) =(-6+-sqrt(-48))/-2 =(-6+-4sqrt(3)i)/-2 =3+-2sqrt(3)i =3+2sqrt(3)i, =3-2sqrt(3)i . Ed Answer by ewatrrr(10682)   (Show Source): You can put this solution on YOUR website! ``` Hi As important as correctly using the quadratic formula is starting with the correct quadratic equation to apply it to: -x^2+6x-21=0 |Must multiply ALL terms by -1 to proceed in tha fashion x^2 - 6x + 21 = 0 x^2+6x-21=0 |If... this were the correct quadratic (using as an example) -6+-sqrt(120)/(2) -6+-sqrt(4*30)/(2) -6+-2sqrt(30)/(2) -3+-sqrt(30) |important to take the 'sqrt(4)out front' ```